2007
DOI: 10.1653/0015-4040(2007)90[249:tradeo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Residual and Direct Effects of Reduced-Risk and Conventional Miticides on Twospotted Spider Mites, Tetranychus Urticae (Acari: Tetranychidae) and Predatory Mites (Acari: Phytoseiidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…Twospotted spider mites were observed to aggregate on the older trifoliates (mean number of TSSM motiles was 160.0 § 18.0 per trifoliate on untreated trifoliates). Neoseiulus californicus may have dispersed to areas of high prey density within the plant, possibly due to olfactory response to kairmones emitted from TSSM infested leaves (Dicke and Sabelis 1988;Liburd et al 2007). …”
Section: The 2006-2007 Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Twospotted spider mites were observed to aggregate on the older trifoliates (mean number of TSSM motiles was 160.0 § 18.0 per trifoliate on untreated trifoliates). Neoseiulus californicus may have dispersed to areas of high prey density within the plant, possibly due to olfactory response to kairmones emitted from TSSM infested leaves (Dicke and Sabelis 1988;Liburd et al 2007). …”
Section: The 2006-2007 Trialmentioning
confidence: 99%
“…As a type II generalist, N. californicus can adapt to Xuctuations in prey populations and temperature, providing consistent pest suppression Greco et al 2005;Escudero and Ferragut 2005). Easterbrook (1992), , Escudero and Ferragut (2005), and Liburd et al (2007) have demonstrated that N. californicus is tolerant to many insecticides and fungicides, and is able to remain viable at temperatures from 10°C to approximately 32°C (Hart et al 2002). Rhodes et al (2006) found that N. californicus is able to maintain more consistent control of TSSM populations compared with P. persimilis throughout the season in north Florida strawberry Welds.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, control of TSSM populations is done mainly by pesticides, but in some cases pesticide sprays make the pest problem even worse because they negatively affect natural enemies (Liburd et al 2007). Furthermore, strains of TSSM resistant to pesticides are selected, making chemical control more difficult (Sato et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although several pesticides targeted at T. urticae have different side effects on N. californicus (Bittencourt Monteiro 2001, Sato et al 2002, Castagnoli et al 2005, Liburd et al (2007) have reported that Acramite 1 (binfenazate) had low toxicity towards predatory mites, and was recommended for use in combination with the predatory mites for the control of T. urticae on strawberries (Rhodes and Liburd 2006). Similarly, Cloyd et al (2006) and Liburd et al (2007) found that bifenazate was not toxic to N. californicus.…”
Section: Discussionmentioning
confidence: 99%